Graphene-Based Flexible Sensors for Simultaneous Detection of Ascorbic Acid, Dopamine, and Uric Acid - Meng, Shuaishuai; Liu, Yaming; Wang, Li; Ji, Xixi; Chen, Yun; Zheng, Tingting; Yu, Jie; Feng, Huanhuan (Frontiers in Bioengineering and Biotechnology, 2021)
Many diseases are closely related to abnormal concentrations of ascorbic acid (AA), dopamine (DA), and uric acid (UA). Therefore, the development of tools to detect the concentrations of these small molecules is significant to investigate the normal life activities of organisms. Electrochemical detection has been widely used for the detection of small molecules due to its good selectivity, high sensitivity, and low cost. The fabrication and development of flexible materials are the main focus of electrochemical sensing research. Graphene (GN) is very suitable for electrochemical sensing materials due to its excellent catalytic performance and large specific surface area. Hereby, three-dimensional (3D) GN nanosheets were grown on soft carbon cloth (CC) to fabricate GNSs/CC by thermal chemical vapor deposition (CVD) and further loaded the reaction center with the active site of GN, successfully realized simultaneous detection of three small molecules of AA, DA, and UA. Moreover, the GNSs/CC electrodes show high oxidation peak currents. It has been successfully applied to the detection of UA in human serum, and the recovery is between 104% and 124%. Therefore, the electrode is expected to be applied to the real-time detection of UA in real blood samples.